THE ASSOCIATION BETWEEN BIRTH WEIGHT AND THE OCCURRENCE OF PERINEAL RUPTURE IN TALANG PUBLIC HEALTH CENTER, TEGAL DISTRICT - Tri Agustina Hadiningsih; Ika Esti Anggraeni (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
The weight of the newborn is a risk factor for perineal tearing when spontaneously delivered. This is because the perineum is not strong enough to withstand stretching of the baby's head when the baby weighs a considerable amount. According to the data obtained from Talang Public Health Center, in the number of births in January - October 2021, 28% of mothers experienced perineal rupture during vaginal delivery. This study aimed to determine the relationship between newborn weight and the incidence of perineal rupture. A quantitative with a correlational design was used in this research. The data was collected from January to May 2022 in Talang Public Health Center. The sample used in this research was 119 mothers who gave birth. We used secondary data and analyzed it using SPSS with the chi-square statistical test. Based on the research results, it can be concluded that there is no significant relationship between the birth weight of the baby and the incidence of perineal rupture in Talang Health Center with the value of p = 0.650 α = 0.05. This may be due to other factors such as maternal, fetal, birth, and birth assistance factors. Hopefully, this research will provide health workers and the community with knowledge so pregnant women can have regular ANC visits to monitor fetal development.